Analysis of Flavonoids in Oncidium Taka Flowers at Various Stages of Development - Megat Mohd Tahir, Putri Noor Faizah (2006)
Colour is an important factor in determining the aesthetic value, and hence the economic value of flowers. Thus there is active research and development in chemistry of colour pigments especially in flowers and in the breeding of cultivars for preferred colors. Understanding the chemistry of colour pigments, especially the changes in their composition and concentration as the flower develops, is essential as a background for any attempt at genetic manipulation of flower colour. It is important to know which pigments are normally present so that specific steps in their synthesis can be targeted. In this study the concentration of flavonoids in the flower of the orchid Oncidium Taka, as it develops fiom the bud stage to the mature flower, was determined. Four stages of flower development were arbitrarily selected, viz. the bud stage, partially open flower, fully opened flower and the mature flower. The flavonoids were extracted using methanol and the extract concentrated to dryness. The separation step was by TLC followed by analysis using HPLC and UV Vis spectrophotometer. The standard compounds for flavonoids were kaempferol, luteolin, naringenin and myricetin. The HPLC analysis result showed that kaempferol, luteolin and myricetin were detected in at the level of 14.54 * 3.86, 1.80 0.27 and 3.04 * 1.51 pglg FW respectively at the bud stage. Throughout the experiment, kaempferol concentration decreased as the flower developed to maturity (0.12 0.03 pg/g FW). The same trend was also observed for myricetin (0.24 * 0.1 1 pglg FW) at the third stage but increased at the fourth stage. Luteolin on the other hand remained consistent at approximately 1.35 * 0.44 pg/g FW throughout the development of the flower fiom the bud to the mature stage. Naringenin could not be detected using HPLC at all stages of flower development. The qualitative analysis using TLC and W Vis spectrophotometer also indicated the presence of kaempferol, luteolin and myricetin in Oncidium Taka petals extract. Naringenin was only detected using TLC technique with solvent A (chloroform:acetic acid:water (90:45:6 vlvlv)) and solvent C (chloroform:methanol(100:20 vlv)). All the TLC plates were fumed with iodine vapour.